Potential role of soluble CD40 receptor in chronic inflammatory diseases - Wagner, Andreas H.; Klersy, Anton; Sultan, Cheryl Sophia; Hecker, Markus (Biochemical pharmacology, 2023)
The CD40 receptor and its ligand CD154 are widely expressed in various immune-competent cells. Interaction of CD154 with CD40 is essential for B-cell growth, differentiation, and immunoglobulin class switching. Many other immune-competent cells involved in innate and adaptive immunity communicate through this co-stimulatory ligand-receptor dyad. CD40-CD154 interaction is involved in the pathogenesis of numerous inflammatory and autoimmune diseases. While CD40 and CD154 are membrane-bound proteins, their soluble counterparts are generated by proteolytic cleavage or alternative splicing. This review summarises current knowledge about the impact of single nucleotide polymorphisms in the human CD40 gene and compensatory changes in the plasma level of the soluble CD40 receptor (sCD40) isoform in related pro-inflammatory diseases. It discusses regulation patterns of the disintegrin metalloprotease ADAM17 function leading to ectodomain shedding of transmembrane proteins, such as pro-inflammatory adhesion molecules or CD40. The role of sCD40 as a potential biomarker for chronic inflammatory diseases will also be discussed.
Gesehen am 22.08.2024
Online publiziert: 18 October 2023